Demographic, Behavioral, and Social Characteristics Associated With Smoking and Vaping Among Men Who Have Sex With Men in San Francisco. Issue 3 (1st May 2019) - Santos, Glenn-Milo; Tan, Judy; Turner, Caitlin; Raymond, H. Fisher
Tobacco use is the leading lifestyle-related cause of death in the United States. We analyzed correlates of smoking and vaping tobacco in the National HIV Behavioral Surveillance (NHBS) among men who have sex with men (MSM) in San Francisco in 2014 ( n = 410) using multivariable logistic regression models. We found that more than two in five MSM (41%) smoked or vaped. Smoking was greater for men of color (46% vs. 35%; p = .02); those with annual income below $50, 000 (47% vs. 34%; p = .01); those without a college education (51% vs. 30%; p < .01); and the uninsured (55% vs. 38%; p = .04). In multivariable analyses, greater odds of smoking were observed among men living with HIV (adjusted odds ratio [aOR] = 1.7; 95% CI [1.00, 2.8]); men who reported cocaine use (aOR = 3.1; 95% CI [1.9, 5.0]), and men who reported greater number of alcohol drinks on a drinking day (aOR = 1.2; 95% CI [1.05, 1.29]). Lower odds of smoking were observed for men who completed college (aOR = 0.57; 95% CI [0.36, 0.88]). Greater odds of vaping were observed among men who reported meth use (aOR = 3.01; 95% CI [1.65, 5.50]). Lower odds of vaping were observed among men who completed college (aOR = 0.55; 95% CI [0.32, 0.98]). In conclusion, the prevalence of smoking and vaping among MSM is extremely high, particularly HIV-positive MSM. MSM who smoked and vaped were more likely to be racial and ethnic minorities, have lower socioeconomic status, and report more substance and alcohol use. These findings highlight the need to develop strategies effectively addressing the high rates of cigarette smoking and vaping among MSM, particularly among minority MSM and MSM living with HIV.